PENGARUH KUALITAS PELAYANAN DAN PRODUK TERHADAP MINAT BELI INDUSTRI GENTENG UD SUHADI KABUPATEN TULUNGAGUNG - Kelvin Bagus Eka Pradana; Nafik Umurul Hadi; Soelistyo Soetji Handajanti (Jurnal Cita Ekonomika, 2022)
Industry in the current era, makes us understand that the level of business competition is becoming increasingly high. The number of people who use tile products, the quality is a priority and very important to win the competition. By understanding what consumers want and expect from the quality provided, it will get an added value for the owner. This study aims to determine: the effect of service quality and product quality on buying interest in the UD Suhadi tile industry in the Nganti Village area, Boyolangu District, Tulungagung Regency. This research paradigm uses positivistic (quantitative) with a descriptive approach. The test data is primary data. The research population carried out by this researcher was all consumers of the tile industry from January to May 2022, random sampling method. Data collection techniques using a questionnaire. The data analysis tool used is Partial Least Square (PLS) data analysis. The results of this study indicate that: 1. Based on the evaluation results of the measurement model that the variables X1, X2 and Y a total of 13 indicators are declared valid. 2. Based on the results of hypothesis testing, the service quality and product quality variables have a significant influence on the latent variable of buying interest.